Immobilization of Fe-Doped Ni2P Particles Within Biomass Agarose-Derived Porous N,P-Carbon Nanosheets for Efficient Bifunctional Oxygen Electrocatalysis - Xiao, Yifan; Deng, Sihui; Li, Meng; Zhou, Qixing; Xu, Libang; Zhang, Huaifang; Sun, Dongmei; Tang, Yawen (Frontiers in Chemistry, 2019)
A feasible and green sol-gel method is proposed to fabricate well-distributed nano-particulate Fe-Ni2P incorporated in N, P-codoped porous carbon nanosheets (Fe-Ni2P@N,P-CNSs) using biomass agarose as a carbon source, and ethylenediamine tetra (methylenephosphonic acid) (EDTMPA) as both the N and P source. The doped Fe in Ni2P is essential for a substantial increase in intrinsic catalytic activity, while the combined N,P-containing porous carbon matrix with a better degree of graphitization endows the prepared Fe-Ni2P@N,P-CNSs catalyst with a high specific surface area and improved electrical conductivity. Benefiting from the specific chemical composition and designed active site structure, the as-synthesized Fe-Ni2P@N,P-CNSs manifests a satisfying catalytic performance toward both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in an alkaline solution, with low overpotential, small Tafel slope and long-term durability, relative to the counterparts (Fe-free Ni12P5/Ni2P2O7@N,P-CNSs and CNSs) with single components and even comparable to Pt/C and RuO2 catalysts. The present work broadens the exploration of efficient bifunctional oxygen electrocatalysts using earth abundant biomass as carbon sources based on non-noble metals for low cost renewable energy conversion/storage.